A test of the viability of fluid-wall rock interaction mechanisms for changes in opaque phase assemblage in metasedimentary rocks in the Kambalda-St. Ives goldfield, Western Australia - Evans, Katy (Springer, 2009)
Transitions from pyrrhotite-magnetite- to pyrite-magnetite- and pyrite-hematite-bearing assemblages in metasedimentary rocks in the Kambalda-St Ives goldfield have been shown to be spatially associated with economic gold grades. Fluid mixing, fluid-rock interaction and phase separation have been proposed previously as causes for this association. Textural, mineralogical and isotopic evidence is reviewed, and thermodynamic calculations are used to investigate the mineralogical consequences of progressive fluid-rock interaction in interflow metasediments. Fluid-rock interactions in response to fluid infiltration and/or bulk composition variation are plausible mechanisms for production of the observed features.